Enhancing Ethnomathematics Integration in Mathematics Instruction through Teacher Professional Learning Communities (MGMP) in Maros - Nur Ismiyati; Intan Buhati Asfyra; Syamsinar Syamsinar; Fadhilah Nur Sa'diyyah; Nuratika Rahmat Kalla (Universitas Dehasen Bengkulu, 2026)
This community service activity aimed to strengthen the implementation of ethnomathematics in mathematics instruction through the Subject Teacher Consultation Forum (MGMP) in Maros Regency. The primary challenges faced by the partner group included limited teacher understanding of ethnomathematics concepts and constraints in developing culturally based instructional materials. The program was conducted through workshops and mentoring activities involving mathematics teachers as participants. The implementation stages included observation, planning, execution, and evaluation. The findings indicate a significant improvement in teachers’ understanding and competencies, as evidenced by questionnaire results categorized as “very good” and increased pretest-posttest scores. Furthermore, teachers successfully produced ethnomathematics-based instructional products, such as student worksheets, mathematical literacy problems, and teaching modules contextualized to local culture. The program also enhanced teachers’ practical skills in designing innovative and meaningful learning experiences. Therefore, workshops conducted through the MGMP forum proved effective in improving teacher competencies and supporting the collaborative and sustainable implementation of ethnomathematics-based instruction